Designing a Comprehensive Model for Health Tourism with a Commercial Orientation - Chatrouz, Azadeh; Azad, Naser; Naami, Abdallah (Management Strategies and Engineering Sciences, 2025)
Tourism has become a method of conducting business worldwide, and health tourism, driven by individuals' need for medical treatment, can also contribute to commercialization efforts. This dissertation aims to design a comprehensive model for health tourism with a commercial orientation. The research employs a mixed-methods approach (qualitative-quantitative). In the qualitative phase, grounded theory was utilized with MAXQDA14 software to identify the indicators related to health tourism with a commercial orientation. Participants in the qualitative phase included informed experts with notable insights and publications in the research domain. Based on the theoretical saturation criterion, 16 participants were purposefully selected. In the quantitative phase, a developmental-applied method was employed. The statistical population for the quantitative phase comprised all healthcare professionals and specialist physicians in six selected public and private hospitals. The total statistical population consisted of 1,406 individuals (based on hospital websites). Cochran's formula was applied to determine the sample size for the quantitative phase, resulting in 306 individuals selected through stratified random sampling. The findings culminated in a paradigmatic model comprising six variables: foundational and constitutive factors, phenomenon, developmental factors, strategic factors, limiting factors, and outcomes. In the quantitative phase, among the components, organizational factors exhibited the highest impact (coefficient = 0.889), while healthcare costs had the least impact (coefficient = 0.718). Ultimately, the final model demonstrated that developmental factors had the greatest influence on strategies (coefficient = 0.918), followed by the main phenomenon's impact on strategies (coefficient = 0.917), foundational factors on the phenomenon (coefficient = 0.914), intervening factors on strategies (coefficient = 0.888), and strategies on outcomes (coefficient = 0.619).